Implementation of the Quizizz Application for Learning Media in Nurul Islam Kindergarten Rungkut Asri Timur Surabaya Based on Gamification - Ani Dijah Rahajoe; Agussalim; Hendra Maulana (Nusantara Science and Technology Proceedings, 2022)
The Covid-19 pandemic forces us to continue to innovate and adapt to continue to carry out activities as before the pandemic. This digital adaptation or transformation needs to be done to minimize direct human contact. The educational institution, which is the meeting place for students, and teachers, makes the location quite vulnerable to the spread of Covid19. Educational institutions and university organizers are also encouraged to conduct online learning. Online learning media that can use include Quizizz and Kahoot. Quizizz and Kahoot are used to design quizzes, tests, polls, surveys, or diagnostic tests that can be separated from the primary teaching and learning process or are supplementary. This learning is applied to the teachers of TK Nurul Islam Rungkut Asri Timur Surabaya. During the two days of training, the teachers showed enthusiasm during the training. The methods applied are discussion, demonstration, and hands-on practice. Six kindergarten teachers and two lecturers from UPN “Veteran” Jawa Timur attended this training. The training results show that the method can align the learning media through Quizziz Kahoot with the gamification method for students. The results are indicated by the material presented, including pictures adapted to the student's age. The training results also show that participants can directly practice learning materials for their students, and their students can participate more actively in the gamification process. The feedback showed that all teacher participants stated that learning in Nurul Islam Kindergarten was appropriate, and 83% stated it was easy to implement.